PENATALAKSANAAN HOLISTIK PADA AN. TM USIA 18 TAHUN DENGAN BELLS PALSY MELALUI PENDEKATAN KEDOKTERAN KELUARGA DI WILAYAH KERJA UPTD PUSKESMAS NATAR - Amalia, Shafira; Ernawati, Tutik (Medula, 2024)
Bell palsy is an acute paralysis of the peripheral facial nerve (N. Clinical manifestations caused by Bell's palsy can include impairment, disability, handicap, and entertainment, and can cause mental problems for sufferers. Applying the principles of family medicine services and carrying out holistic management based on a framework for solving patient problems with a patient-centered, family-focused, and community-oriented approach based on Evidence-Based Medicine. This study is a case report using primary data obtained through history taking, physical examination, and home visits to complement family data, and psychosocial and environmental data. Secondary data was obtained from patient medical records. Patient An. TM aged 18 years with complaints of stiffness on the right side of the face since two days ago. The patient has a habit of riding a two-wheeler without using head protection. The patient also had a history of varicella two years ago. Holistic management with a family doctor approach has been carried out for An.TM aged 18 years with Bell's palsy which was adjusted based on the initial holistic diagnosis. Before the intervention, the patient and family are given a pretest to measure the patient's level of knowledge regarding the disease they are suffering from. During the intervention, the patient is explained about the disease he is suffering from using media in the form of posters, and the patient is given education regarding the importance of completing treatment, how to prevent the disease, and doing facial exercises. At the last visit, a posttest was given to the patient and family with the results being a significant increase in knowledge about the disease they were suffering from and awareness of the importance of changing patient habits.